Assessment of performance of retrofitted masonry walls under seismic loading - Seah, Clarisse Xuanli. (2009)
Many unreinforced masonry (URM) buildings in the world suffer from damage or collapse in the event of an earthquake due to insufficient strength or ductility. This deficiency has led to an increasing demand for feasible techniques to upgrade the performance of URM buildings. As such, extensive damage can be minimized by means of strengthening or retrofitting measures which typically give rise to more satisfactory behaviour in masonry walls. This report investigates the in-plane seismic behaviour of URM walls strengthened with canvas sheets. The aim of the experimental programme is to obtain representative force-resisting data and the seismic response of the specimens. For the experiment, two identical URM specimens were built with clay bricks and Grade III mortar comprising 1:1:6 cement-lime-sand ratio. Strengthening was provided on one specimen using OD cotton canvas and contact adhesive. Each specimen was subjected to in-plane cyclic lateral loads for 2 cycles per drift with progressive 0.05 % increments until a 20 % drop in maximum strength was reached. Experimental work showed that the canvas bracing improved the seismic response of the masonry panel. The observed common mode of failure for both specimens was sliding. However, sliding failure was abrupt while the strengthened specimen gradually failed by after several cycles. Subsequently, the unstrengthened specimen failed by rocking and shear while the canvas-braced wall failed by rocking. As such, the canvas delayed the cracking of the bed joint mortar layer and minimized crack propagations induced by shear. From hysteretic behaviour, the strengthened wall exhibited lower stiffness and strength deterioration, less flexural and shear distortion and less twisting in the masonry panel. The strengthened wall also attained a maximum lateral strength 30 % higher than that of the unstrengthened specimen. Thus, the canvas bracing was shown to improve the overall seismic performance of the URM test specimens. The canvas application scheme also showed superior resistance to exposure to heat and humidity by retaining its structural and material integrity over a two-month exposure period.